SISTEM PENDATAAN PASIEN PADA BIDAN PURBA BERBASIS JAVA - Ariando Damanik; Rendi Prasetya; Dian Nazelliana (Fakultas Ilmu Komputer, Unversitas Muhammadiyah Riau, 2020)
Purba Midwives is one of the agencies engaged in the health sector that uses information systems to support activities and patient health services at the Ancient Midwife. The problem that occurs in the Ancient Midwife is that the existing information system is not computerized or is still using manual methods in processing patient data, resulting in accumulation of patient data, inaccurate reporting processes and ineffective and inefficient processing of patient data. Researchers aim to research and assist in solving problems that exist in the ancient midwife, namely, making a patient data collection information system. Making a system at the ancient midwife, researchers used a process model or waterfall method. The research method used by researchers is a qualitative research method by collecting and analyzing data on the ancient midwife. While the system is built using the Java programming language and uses MySQL as a database. In the process of making a patient data processing system, it is hoped that it can assist officers in processing patient data, assist officers in presenting patient data information and making health service reports to be effective and efficient.